DISTRIBUSI MITOKONDRIA DAN EKSPRESI BAX PADA HUVEC’s YANG MENGALAMI APOPTOSIS AKIBAT INDUKSI OX-LDL - Riawan, Wibi; Wibowati, Samodrijanti (Fakultas Kedokteran Universitas Brawijaya, 2006)
ABSTRACT It had been revealed that endothelial dysfunction which is caused by oxydized LDL is related to TNF Receptor Apoptosis Including Ligand (TRAIL) mechanism. However, there is study to see the involvement of mitochondrial mecanism in Ox-LDL endothelial cells dysfunction. This study was done to see the effect of Ox-LDL treatment on apoptosis of HUVEC’s culture whether associated with the distribution of mitochondria or BAX expression, the main protein mitochondria apoptosis mechanism. HUVEC’s culture was divided into two groups: control group and treatment group ( 50 mg/ml Ox-LDL for 24 hours). Doublestaining for DNA fragmented (TUNEL) and BAX expression were done respectively, as well as immunochemistry using monoclonal Ab of mitochondria. In the control group mitochondria was distributed firmly on cytoplasma of endothelial cells. In contrast, mitochondria were only found near nuclear membrane cells on treatment group (this future usually found on divided cells) there was also an increasing of BAX expression and a mount of apoptotic cells on treatment group compared with control group. It can be concluded that mitochondria is involved in apoptosis of Ox-LDL endothelial cells in order to serve the abundant energy. Keywords: Mitochondria distribution, Bax expresson, Apoptotic, Ox-LDL